2001
DOI: 10.1210/jc.86.4.1616
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Orexin Receptors in Human Pituitary

Abstract: Orexins-A and -B are hypothalamic peptides derived from a precursor called prepro-orexin and relationated with the stimulation of food intake. They act on G protein receptors named orexin receptor 1 (OX(1)R) and orexin receptor 2 (OX(2)R), respectively. In the present study, we used RT-PCR and immunohistochemical techniques to detect the presence of OX(1)R and OX(2)R in human pituitary. A band of the expected size for both OX(1)R and OX(2)R was shown in human pituitary by RT-PCR. The cellular localization of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…In addition, OX1R expression was also detected at high level in the pituitary gonadotrope cell line, LβT2. This observation is consistent with studies in rats, human and sheep [39,40,41] supporting the potential role of orexin A in the regulation of reproductive neuroendocrine processes at the pituitary level. Furthermore, we demonstrated that orexin A likely stimulates GnRH mRNA expression and release in vivo by a direct action, using immortalized, GnRH-producing GT1-7 cells in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, OX1R expression was also detected at high level in the pituitary gonadotrope cell line, LβT2. This observation is consistent with studies in rats, human and sheep [39,40,41] supporting the potential role of orexin A in the regulation of reproductive neuroendocrine processes at the pituitary level. Furthermore, we demonstrated that orexin A likely stimulates GnRH mRNA expression and release in vivo by a direct action, using immortalized, GnRH-producing GT1-7 cells in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…This hypothesis is supported by several other lines of evidence. Firstly, orexins and their receptors were recently discovered in the anterior pituitary of both the rat and human, indicating a possible paracrine and/or autocrine role of orexins in modifying somatotropes [14, 15]. Secondly, orexins induced significant changes in the electrophysiological activities of neurons and other cells [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ORX peptide/receptor system was observed in the pituitary (Date et al, 2000; Blanco et al, 2001; Silveyra et al, 2007). The relevance of ORXs in the pituitary is also highlighted by the evidence that ORX-A-like molecule and OX1R are widely present in the adenohypophysis of Xenopus (Suzuki et al, 2007; Chieffi et al, 2014), and this underlines a highly conserved function.…”
Section: Role Of Orexins In Endocrine Systemmentioning
confidence: 99%
“…In the Nile tilapia ( Oreochromis niloticus , Monda et al, 2008; Suzuki et al, 2009), an ORX-B-like substance might be secreted from LH- or TSH-containing cells and might regulate the pituitary function, as well. Blanco et al (2001) detected the presence of ORX-A and ORX-B in the human adenohypophysis cell types. The ORX-A was located in 33% of pituitary cells, including PRL (82 ± 5.3%), TSH (18 ± 2.3%), growth hormone (GH; 10 ± 2.3%), Follicle-Stimulating Hormone (FSH; 8 ± 2.6%) and LH (7 ± 3.2%) cells, but not in corticotrope cells (Monda et al, 2006, 2007).…”
Section: Role Of Orexins In Endocrine Systemmentioning
confidence: 99%